Exploring the potential application of palm methyl ester sulfonate as an interfacial tension reducing surfactant for chemical enhanced oil recovery - Sarveen, M. (Trans Tech Publications Ltd, 2019)
As the petroleum industry is facing challenges to add more oil reserves in their book, greater emphasis has been placed on improving the ultimate recovery factor for oilfields. When the recovery from primary and secondary methods could not be improved further, enhanced oil recovery (EOR) generally will be sought as the last option. One of the techniques applied in EOR is known as surfactant flooding. Though surfactants are very effective for the incremental oil recovery, there are implications during the post-flooding process. EOR surfactants that derived from petrochemicals generally display negative effects towards the marine ecosystem. This initial study aims to evaluate the potential application of palm oil based methyl ester sulfonate (MES) as a possible candidate for EOR application. Three qualitative and quantitative tests were performed on MES to evaluate its properties and capabilities for application in a specific offshore field. The results obtained from the qualitative compatibility and stability tests show that this anionic surfactant has great stability and compatibility with the brine solution as there are no visible signs of precipitation formation. However, the qualitative phase behavior test results indicated that the surfactant solution although has the ability to react with the crude oil but not at the required micro-emulsion state. In addition, the quantitative interfacial tension (IFT) test results also verified and supported the phase behavior test results where the strength of the MES was not adequate as a single surfactant system to achieve the ultra-low IFT state. Â© 2019 Trans Tech Publications Ltd, Switzerland.